Trends in the burden of HIV mortality after roll-out of antiretroviral therapy in KwaZulu-Natal, South Africa: an observational community cohort study - Reniers,G; Blom,S; Calvert,C; Martin-Onraet,A; Herbst,AJ; Eaton,JW; Bor,J; Slaymaker,E; Li,ZR; Clark,SJ; Bärnighausen,T; Zaba,B; et al. (Lancet HIV, 2016)
BACKGROUND: Antiretroviral therapy (ART) substantially decreases morbidity and mortality in people living with HIV. In this study, we describe population-level trends in the adult life expectancy and trends in the residual burden of HIV mortality after the roll-out of a public sector ART programme in KwaZulu-Natal, South Africa, one of the populations with the most severe HIV epidemics in the world. METHODS: Data come from the Africa Centre Demographic Information System (ACDIS), an observational community cohort study in the uMkhanyakude district in northern KwaZulu-Natal, South Africa. We used non-parametric survival analysis methods to estimate gains in the population-wide life expectancy at age 15 years since the introduction of ART, and the shortfall of the population-wide adult life expectancy compared with that of the HIV-negative population (ie, the life expectancy deficit). Life expectancy gains and deficits were further disaggregated by age and cause of death with demographic decomposition methods. FINDINGS: Covering the calendar years 2001 through to 2014, we obtained information on 93903 adults who jointly contribute 53542 8 person-years of observation to the analyses and 9992 deaths. Since the roll-out of ART in 2004, adult life expectancy increased by 15·2 years for men (95% CI 12·4-17·8) and 17·2 years for women (14·5-20·2). Reductions in pulmonary tuberculosis and HIV-related mortality account for 79·7% of the total life expectancy gains in men (8·4 adult life-years), and 90·7% in women (12·8 adult life-years). For men, 9·5% is the result of a decline in external injuries. By 2014, the life expectancy deficit had decreased to 1·2 years for men (-2·9 to 5·8) and to 5·3 years for women (2·6-7·8). In 2011-14, pulmonary tuberculosis and HIV were responsible for 84·9% of the life expectancy deficit in men and 80·8% in wome